Increasing Gojek Customer Satisfaction through Improving Service Quality, Price Perception, and Promotions - Priambodo, Galih; Nainggolan, Bonifasius MH (Majalah Ilmiah Bijak, 2024)
This study aims to analyze the effect of service quality, price perception, and promotion on customer satisfaction of Gojek online transportation services in the Greater Jakarta area. This research uses quantitative methods with data collection techniques through surveys using questionnaires distributed to active Gojek users in Jabodetabek. The population in this study is Gojek users in Jabodetabek who have used the service at least twice. The samples in this study are 230 Gojek users.This study's theoretical concept involves three main variables affecting customer satisfaction: service quality, price perception, and promotion. Data analysis was conducted using regression statistical techniques to test the relationship between these variables using SPSS 26. The study's results stated that service quality, price perception, and promotion both partially and simultaneously positively and significantly affected Gojek customer satisfaction in Jabodetabek. The study results will provide deeper insight into the factors affecting Gojek customer satisfaction in Greater Jakarta. The practical implications of this research can help Gojek management improve aspects of service quality, address price perception, and design more effective promotional strategies to increase customer satisfaction. In addition, the research is expected to contribute to further understanding in marketing and service management, especially in the dynamic and competitive online transportation industry.